Efeitos da ciclosporina a sobre a função renal de cães da raça Golden Retriever normais ou afetados pela distrofia muscular - Morini, Adriana Caroprezo; Miglino, Maria Angélica; Carvalho, Marileda Bonafim [UNESP]; Martins, Daniele dos Santos; Ambrósio, Carlos Eduardo; Casagrande, Carla Fabiana; Catelli, Alida Abatemarco; Souza, Ana Paula [UNESP]; Luppi, Martha Maria Circhia Pinto; Gaiad, Thaís Peixoto; Zatz, Mayana (My University, 2008)
The muscular dystrophy of Golden Retriever is a degenerative miopaty caused by the absence of dystrophy and it is genetically homologue of the Duchenne muscular dystrophy in humans, so, these dogs are considerably experimental models for studies on cellular therapy. Their successful depends of the adequate immunosuppression. Cyclosporin A is indicated for that and the monitoring of blood concentration and adverse effects are essential to viabilise the therapy. It was studied GRMD dogs, and normal dogs from the same breed, submitted for therapy with CsA, associated, on GRMD, of cell transplantation. It was evaluated the possible effects of the drug on renal functions. It has been considerate the clinic manifestations, urinalisis, testis of glomerular function and blood concentrations of urea, cretinine, sodium and potassium. In our results we found a discrete increase of blood urea on booth groups; increased levels of urine's cylinders and protein and also increase of urinary density on GRMD group. CsA therapy could make acute lesions on renal tubules, especially on GRMD. These dogs also have different reactions than normal dogs on relation of ions homeostasis and renal function. However, earlier diagnosis and adequate treatment could prevent the development of renal diseases.
Effect of cyclosporin A on renal functions of normal Golden Retriever dogs or Golden Retriever with muscular dystrophy
Keywords: Immunosuppression; Nefrototoxicity; Canis familiaris